Formulation and Evaluation of the Antioxidant Activity of an Emulsion Containing a Commercial Green Tea Extract - Anna Sykuła; Izabela Janiak-Włodarczyk; Ireneusz Tomasz Kapusta (Molecules)
The addition of an extract to an emulsion is intended to improve its fragrance and care qualities. Green tea is a beverage known all over the world. It is tasty and has beneficial effects on human health due to its high polyphenol content. The compounds present in this variety of tea have also made it an interesting cosmetic ingredient. The polyphenols contained in green tea have antioxidant properties and can delay the ageing process in human skin. Various preparations with this ingredient can be found on the market—from creams to hair care products. Making one’s own cosmetics is also a trend. In the following study, three creams containing green tea extracts from three different manufacturers were prepared, and the total polyphenol (TP) contents, the phenolic profile of the extracts used and the antioxidant activity of these preparations were examined using two methods: DPPH• and ABTS•+ cationic radicals. The study showed that the antioxidant activity of the glycerin–water extracts measured by the selected methods was higher than that of the oil extract. Among the creams, the product with green tea extract from Firm 2 (glycerin–water extract) showed the best antioxidant properties.